Out of left field? Explaining the variable electoral success of European radical left parties. (January 2015) - March, Luke; Rommerskirchen, Charlotte
European radical left parties (RLPs) are gradually receiving greater attention. Yet, to date, what has received insufficient focus is why such parties have maintained residues of electoral support after the collapse of the USSR and why this support varies so widely. This article is the first to subject RLPs to large-n quantitative analysis, focusing on 39 parties in 34 European countries from 1990 to 2008. It uses the 'supply and demand' conceptual framework developed for radical right parties to identify a number of socio-economic, political-cultural and party-system variables in the external environment that might potentially affect RLP support. The article finds the most persuasive variables to include political culture (past party success), the level of unemployment, Euroscepticism and anti-globalization sentiment, the electoral threshold and competition from Green and radical right parties. The findings suggest several avenues for future research and provide a framework that can be adapted to explain the electoral success of other party families.